Nghiên cứu điều chế hydrogel nhạy nhiệt trên cơ sở copolyme ghép chitosan-pluronic F127 định hướng ứng dụng trong chữa lành vết thương - Bích Trâm, Nguyễn Thị; Lệ Hằng, Đặng Thị; Thu Thắm, Lê Thị; Hải, Nguyễn Đại; Khoa, Nguyễn Cửu; Quyển, Trần Ngọc (Vietnam Journal of Chemistry, 2016)
In recent years, injectable chitosan-based hydrogels have been widely studied towards biomedical applications because of their potential performance in drug/cell delivery and tissue regeneration. In this study, a temperature-sensitive bio-hydrogel based on chitosan and pluronic was synthesized. The structure of copolymer was characterized by IR and 1H-NMR spectroscopy. The sol-gel phase transition behavior of hydrogel was rheology method. The in vitro experiments showed that, the solutions of chitosan-pluronic F127 were changed to gel stage to gel stage when the temperature increased from 25 oC to 40 oC. The result is a prerequisite for the interesting studies of this complex hydrogel.